Ultra-high-speed dynamics of acoustic droplet vaporization in soft biomaterials: Effects of viscoelasticity, frequency, and bulk boiling point - Bachir A. Abeid; Mario L. Fabiilli; Jonathan B. Estrada; Mitra Aliabouzar (Ultrasonics Sonochemistry, 2024)
Phase-shift droplets are a highly adaptable platform for biomedical applications of ultrasound. The spatiotemporal response of phase-shift droplets to focused ultrasound above a certain pressure threshold, termed acoustic droplet vaporization (ADV), is influenced by intrinsic features (e.g., bulk boiling point) and extrinsic factors (e.g., driving frequency and surrounding media). A deep understanding of ADV dynamics is critical to ensure the robustness and repeatability of an ADV-assisted application. Here, we integrated ultra-high-speed imaging, at 10 million frames per second, and confocal microscopy for a full-scale (i.e., from nanoseconds to seconds) characterization of ADV. Experiments were conducted in fibrin-based hydrogels to mimic soft tissue environments. Effects of fibrin concentration (0.2 to 8 % (w/v)), excitation frequency (1, 2.5, and 9.4 MHz), and perfluorocarbon core (perfluoropentane, perfluorohexane, and perfluorooctane) on ADV dynamics were studied. Several fundamental parameters related to ADV dynamics, such as expansion ratio, expansion velocity, collapse radius, collapse time, radius of secondary rebound, resting radius, and equilibrium radius of the generated bubbles were extracted from the radius vs time curves. Diffusion-driven ADV-bubble growth was fit to a modified Epstein-Plesset equation, adding a material stress term, to estimate the growth rate. Our results indicated that ADV dynamics were significantly impacted by fibrin concentration, frequency, and perfluorocarbon liquid core. This is the first study to combine ultra-high-speed and confocal microscopy techniques to provide insights into ADV bubble dynamics in tissue-mimicking hydrogels.